Anesthetic managements, morbidities and mortalities in retroperitoneal sarcoma patients experiencing perioperative massive blood transfusion - Wang, Jun; Chen, Jun; Liu, Kunpeng; Zhang, Hua; Wei, Yue; Suo, Libin; Lan, Shuang; Wang, Yanzhen; Luo, Chenghua; Yao, Lan (Frontiers in Oncology, 2024)
Objective Given high risks of major bleeding during retroperitoneal sarcoma(RPS) surgeries, severe complications and deaths are common to see perioperatively. Thus, effective anesthetic management is the key point to ensuring the safety of patients. This study aimed to introduce anesthesia management and mortalities in RPS patients receiving massive blood transfusions during surgeries. Methods Records of RPS surgeries under general anesthesia from January 2016 through December 2021 were retrospectively retrieved from our database. Patients who received massive blood transfusions (MBT) exceeding 20 units in 24h duration of operations were finally included in this study. Demographics, modalities of anesthesia management, blood loss, transfusion, peri-anesthesia biochemical tests as well as morbidities and mortalities were collected. Risk factors of postoperative 60d mortality were determined through logistic regression in uni-and multi-variety analysis using the statistics software STATA 17.0. Results A total of 70 patients (male 31) were included. The mean age was 50.1 ± 15.8 years. All patients received combined resections of sarcoma with involved organs under general anesthesia. Mean operation time and anesthesia time were 491.7 ± 131.1mins and 553.9 ± 132.6mins, respectively. The median intraoperative blood loss was 7000ml (IQR 5500,10000ml). Median red blood cells (RBC) and fresh frozen plasma (FFP) transfusion were 25.3u (IQR 20,28u), and 2400ml (IQR 2000,3000ml), respectively. Other blood products infusions included prothrombin complex concentrate (PCCs), fibrinogen concentrate (FC), platelet(plt) and albumin(alb) in 82.9% (58/70), 88.6% (62/70), 81.4% (57/70) and 12.9% (9/70) of patients. The postoperative severe complication rate(Clavien-Dindo grade≥3a) was 35.7%(25/70). A total of 7 patients (10%) died during the postoperative 60-day period. BMI, volumes of crystalloid infusion in anesthesia, and hemoglobin and lactate levels at the termination of operation were found significantly associated with postoperative occurrence of death in univariate analysis. In logistic multivariate analysis, extended anesthesia duration was found associated with postoperative venous thrombosis embolism (VTE) and severe complication. The lactate level at the immediate termination of the operation was the only risk factor related to perioperative death (p<0.05). Conclusion RPS patients who endure MBT in surgeries face higher risks of death postoperatively, which needs precise and effective anesthesia management in high-volume RPS centers. Increased blood lactate levels might be predictors of postoperative deaths which should be noted.